Humoral immunogenicity induced by homologous and heterologous SARS-CoV-2 vaccination schedules - Lozada-Requena, Iván (2025)
Objective: To evaluate the humoral immunogenicity induced by homologous and heterologousvaccination schedules through a comparison of two methods for detecting IgG antibodies againstSARS-CoV-2. Materials and methods: Serum concentrations of specific IgG antibodies targetingthe receptor-binding domain (RBD) of the SARS-CoV-2 spike protein were measured. Samples werecollected from 60 individuals who received different COVID-19 vaccination schedules establishedby the Peruvian health system. Additionally, 20 pre-pandemic serum samples were retrieved froma serum bank. An enzyme-linked immunosorbent assay (ELISA), considered the reference standardtest for such measurements, was used. Additionally, OJABIO rapid diagnostic test kit (PRO) was alsoemployed to qualitatively assess the IgG response. The sensitivity, specificity, positive predictivevalue (PPV), negative predictive value (NPV), Cohen’s kappa and Wilson-Brown interval for the PROtests were calculated and compared with those obtained for ELISA. Results: Both the qualitative(PRO) and quantitative (ELISA) tests detected specific IgG antibodies against the spike protein inall vaccinated individuals. ELISA results indicated that IgG concentrations were not affected by the type of vaccination schedule or the time since the last dose. Prior SARS-CoV-2 infection also had no significant effect on antibody levels. The PRO test demonstrated high sensitivity and specificity, with adequate PPV and NPV. Conclusions: The homologous andheterologous SARS-CoV-2 vaccination schedules induced similar IgG antibody concentrations and half-life, with potential neutralizing capacity, as confirmed by both a quantitative assay and a high-performance qualitative assay. The potential impact of homologous and heterologous vaccination schedules on IgG antibody subclasses remains an area of interest for further research.